A Comparative Study Between Conservative And Modified Radical Mastectomy Which Followed In Management Of Early Breast Cancer Regarding To Recurrence - سعد, أحمد; سليمان, جمال; ابراهيم, علاء (Latakia University Journal -Medical Sciences Series, 2021)
Introduction: Breast cancer is the most common invasive cancer in females, and it is the main cause of cancer deaths in females between the ages of 20-52 years, and it constitutes 30% of all cancers in females. The objective: Comparison of recurrence rates (local, distant) between conservative and modified radical mastectomy in early breast cancer (stage 1,2), and study the relationship between recurrence and tumor histological classification between the two study groups. Methods and materials: A retrospective study. The research sample included 140 patients with early breast cancer, 112 patients who underwent modified radical mastectomy and 28 patients who underwent conserving breast surgery. Results: 4 cases (14.3%) local recurrence, 3 cases (10.7%) distant metastasis in the conservative excision group, 11 cases (9.8%) local recurrence and 20 cases (17.9%) distant metastasis in the modified radical mastectomy group. We found that there was no statistically significant difference between the two study groups with respect to local recurrence (P value =0.4) and distant metastasis (P value =0.3). Our study revealed a statistically significant difference between the two groups in terms of local recurrence (66.7, 16.7%, respectively) according to the histological classification of the tumor G3 (P-value = 0,003) Conclusion: Conservative mastectomy is a convenient and similar procedure in terms of outcomes for modified radical mastectomy in early breast cancer with respect to recurrence rates. The G3 histological classification score constituted a risk factor for local recurrence in the conservative surgery group compared to the modified radical mastectomy group.